DEVELOPMENT OF REGIONAL LABOUR MARKETS IN CONDITIONS OF DECENTRALIZATION - TKACHENKO, Lidiia (Economy and Sociology, 2021)
The decentralization reform in Ukraine began in 2014 and is aimed at implementing the provisions of the European Charter of Local Self-Government, which provides for the redistribution of powers, resources and responsibilities on the basis of subsidiarity. Currently, local governments are endowed with powers and instruments of influence on enterprises located on their territory, but employment and labour market policies remains the prerogative of the central government. For a comparative analysis of the development of regional labour markets in the context of decentralization, labour force survey indicators are more appropriate, since they reflect the actual policy results from the perspective of households. For the 2015–2019 period in most regions of Ukraine, there was an increase in the level of employment and a decrease in the level of unemployment; at the same time, the gender gap in employment has increased in 16 of 25 regions; the sectoral structure of employment continues to stagnate. Some regions have significantly increased the coverage of public works, but this may indicate not the activity of territorial communities, but the lack of stable employment opportunities. Local self-government bodies should play a key role in the formation and implementation of local employment and the labour market policies, their interaction with the state employment service requiring a corresponding transformation.